2011
DOI: 10.1002/mrd.21366
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine alleviates the deterioration of Ca2+ release mechanisms and fragmentation of in vitro‐aged mouse eggs

Abstract: The developmental competence of mammalian eggs is compromised by postovulatory aging. We and others found that in these eggs the intracellular calcium ([Ca2+]i) responses required for egg activation and initiation of development are altered. Nevertheless, the mechanism(s) underlying this defective Ca2+ release is not well known. Here, we investigated if the function of IP3R1, the major Ca2+ release channel at fertilization, was undermined in in vitro aged mouse eggs. We found that in aged eggs IP3R1 displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 99 publications
2
41
2
2
Order By: Relevance
“…However, post-ovulatory aged oocytes experience a decline in IP 3 receptor/channel functionality (Zhang et al 2011), as well as suppressed ER Ca 2C -ATPase activity, and exhibit a consequential depletion of Ca 2C stores that reside within the ER (Takahashi et al 2000). As a result of this impaired Ca 2C homoeostasis, aged oocytes exhibit abnormal Ca 2C oscillations at fertilization that have significantly higher frequency and lower amplitude than those of fertilized fresh oocytes (Igarashi et al 1997, Takahashi et al 2003.…”
Section: Decreased Fertilization Ratementioning
confidence: 99%
See 3 more Smart Citations
“…However, post-ovulatory aged oocytes experience a decline in IP 3 receptor/channel functionality (Zhang et al 2011), as well as suppressed ER Ca 2C -ATPase activity, and exhibit a consequential depletion of Ca 2C stores that reside within the ER (Takahashi et al 2000). As a result of this impaired Ca 2C homoeostasis, aged oocytes exhibit abnormal Ca 2C oscillations at fertilization that have significantly higher frequency and lower amplitude than those of fertilized fresh oocytes (Igarashi et al 1997, Takahashi et al 2003.…”
Section: Decreased Fertilization Ratementioning
confidence: 99%
“…The functionality of the mitochondria does, however, become compromised with extended periods of time following ovulation, a factor that is thought to heavily influence oocyte quality. Diminished mitochondrial integrity in the in vitro aged oocyte has been demonstrated by a loss of mitochondrial membrane potential (Zhang et al 2011) and a decline in levels of ATP production (Chi et al 1988).…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Marutino et al observed that oocyte energy/oxidative status was affected by within/ between-subject, in vivo versus IVM and age-related variations [8]. Moreover, it was confirmed that oocytes aged in vitro exhibited decreased mitochondrial membrane potential and Ca 2+ levels in the endoplasmic reticulum, and that addition of caffeine ameliorates most of these aging-associated changes [9].Thus far, mitochondrial function in mammalian oocytes has been assessed by analyzing mitochondrial localization ATP content and mitochondrial membrane potential [7,10,11]. However, these techniques can be disruptive and are indirect methods for assessing physiological mitochondrial function.…”
mentioning
confidence: 93%